Karakteristik Bahasa Teks SMS Kolom “Lapor Cik” Harian Rakyat Bengkulu - Syaiful Abid (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
The purpose of this study was to describe a precise, in-depth, and detailed understanding of, 1) the use of language in the SMS text of the "Lapor Cik" column of the Harian Rakyat Bengkulu, in terms of formality, the use of slang (slang), word abbreviations, (2 ) the style of language used in the SMS text of the "Lapor Cik" column of the Harian Rakyat Bengkulu. This type of research is descriptive research. The analytical tool used is qualitative, namely by interpreting the meaning contained in the SMS text. The results showed that: 1) the use of the SMS language "Lapor Cik" there are several language uses, namely formal language with a percentage of 0.03%, the use of a foreign language that includes Indonesian, or often referred to as language mixing with a percentage of 0.02%, the use of slang with a percentage of 0.14%, and abbreviation of words with a percentage of 0.34%, meaning that from the overall use of the SMS language "Lapor Cik" is dominated by abbreviations. Then, 2) shortening the language of the SMS "Lapor Cik" using clipping as a part of the process of forming new words, while in the context of SMS Lapor Cik, clipping is used not to form new words, but to save characters and of course credit, and (3) on the styles that can be found in the "Lapor Cik" SMS of the Harian Rakyat Bengkulu, namely: (a) oppositional figure of speech, (b) comparative language style, (c) and linked language style.